Origin and pathogenicity variation of Plasmopara viticola in China - Wu, Wei; Chen, Yuchen; Huang, Huimin; Li, Rongfang; Yang, Bohan; Lv, Junli; Yin, Ling; Qu, Junjie; Song, Shiren; Peng, Yachun; Fu, Peining; Lu, Jiang (Frontiers in Microbiology, 2025)
Grapevine downy mildew caused by Plasmopara viticola (Pv) is one of the most devastating diseases of grapevine in China. To understand the origin and pathogenicity of Chinese Pv, a total of 193 single-sporangiophore isolates were obtained from 14 Chinese major viticulture areas. Phylogenetic analyses suggest that Chinese Pv isolates originate from North America and belong to the P. viticola clade aestivalis. Host range experiments reveal that Chinese Pv are able to infect a wide range of Vitis species from different geographic origins, including Eurasian species Vitis vinifera, North American species V. aestivalis, V. riparia, and V. rupestris, and East Asian Vitis species V. davidii, V. amurensis, and V. hancockii. Analyses of the interactions between Pv isolates and grapevines reveal that the virulence of Pv isolates is correlated with the occurrence time and magnitude of hypersensitive response-mediating leaf necrosis in grape leaves caused by Pv. These understandings of genetic diversity and pathogenicity of Chinese Pv isolate would be useful to develop strategies for controlling grapevine downy mildew spread.